To Talk or not to Talk About Existential Questions - An Interview Study With Elderly Persons and Patients With Fatal Disease - Bäckersten, Carl; Nyblom, Stina; Molander, Ulla; Benkel, Inger (American journal of hospice & palliative medicine, 2025)
Existential experiences often come to the fore in the case of a severe and/or life-threatening disease and in old age. This can evoke a variety of thoughts and emotions. The existential dimension is a concept that encompasses spiritual, religious and secular perspectives. The aim of this study was to gain a deeper understanding of how patients describe the existential dimension of life and whether and in what way the existential questions are raised in conversations and other forms of support within care. A qualitative design, with in-depth semi-structured interviews with patients admitted to an out-clinic oncology department at one hospital and participants living in a nursing home. The interviews were analysed using qualitative content analysis. A total of 15 persons were interviewed. The respondents varied in age from 44 to 96. Two main themes emerged: What are existential questions? and Talk about existential questions. The existential questions refer to life as a whole and death as an end of life. It was summarized into three subcategories: and . About half of the participants thought it was important to talk about existential questions. They wanted to choose who to talk to, when and about what. Support was received from loved ones, professionals and experiences beyond conversations. The study provide new knowledge of how patients and elderly experience the existential dimension. The respondents emphasized a desire to be selective with whom they shared these questions and thoughts.